Pola Pikir Bertumbuh dalam Pembelajaran Matematika: Studi pada Mahasiswa Calon Guru melalui Lesson Study - Ratri Asmaya Puspa; Rastina Kurniasari; Mochamad Lukman Hakim; Surya Sari Faradiba; Miftahul Khasan; Siti Ambarwati (Mathematics Education Study Program, 2026)
This study aims to analyze the growth mindset of prospective mathematics teachers based on learning transcripts from Lesson Study activities on quadratic equations. A qualitative case study approach with thematic analysis was employed to examine classroom interactions, focusing on responses to errors, learning strategies, effort, and teacher feedback. The findings indicate that a growth mindset began to emerge through several key indicators: acceptance of mistakes as part of the learning process, active cognitive engagement such as asking clarification questions, constructive process-oriented feedback from teachers, and collaborative group discussions. However, the study also identified inconsistent pedagogical practices, particularly the use of generalized negative feedback focusing solely on final answers, which potentially reinforces a fixed mindset. The results highlight that while Lesson Study provides an effective collaborative platform for developing a growth mindset, strengthening pedagogical communication competence is essential for prospective teachers to consistently apply growth mindset principles. This study contributes empirical evidence on how growth mindset manifests in authentic classroom settings and underscores the importance of reflective practices in teacher education.